2020
DOI: 10.1055/a-1269-0000
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lumbar Modifiers on Functional and Radiological Outcomes in the Brace Treatment of Lenke Type 1 Adolescent Idiopathic Scoliosis

Abstract: Background Brace treatment prevents the progression of scoliosis and reduces surgical treatment rates. However, the efficacy of brace treatment varies depending on the patientʼs age, gender, curve magnitude and type, structure of the curve, and patient compliance at the beginning of treatment. Methods Between January 2009 and April 2015, 106 Lenke type 1 AIS consecutive patients (69 females, 37 males) who were treated with a brace were examined in three groups according to Lenke classification lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Auerbach et al [34] used the SRS-22 questionnaire to access scoliotic patients' body image disturbance and patients scored the lowest in the self-image domain, which is in concordance with our results, and other studies [35,36]. Other studies using the ODI questionnaire also showed that participants have a minimal disability and are capable of most living activities, for instance, Bayrak et al [37] reported 13/100, and Lange et al [38] reported 8/100, compared to our results of 8.8/100. Leszczewska et al [39] found that patients treated with brace suffer from stress more than patients with physiotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Auerbach et al [34] used the SRS-22 questionnaire to access scoliotic patients' body image disturbance and patients scored the lowest in the self-image domain, which is in concordance with our results, and other studies [35,36]. Other studies using the ODI questionnaire also showed that participants have a minimal disability and are capable of most living activities, for instance, Bayrak et al [37] reported 13/100, and Lange et al [38] reported 8/100, compared to our results of 8.8/100. Leszczewska et al [39] found that patients treated with brace suffer from stress more than patients with physiotherapy.…”
Section: Discussionsupporting
confidence: 92%